Walter Benjamin e la critica all’ideologia del progresso come paradigma della modernità - Picchi, Ludovica (B@belonline, 2024)
This article aims to show how Walter Benjamin’s critique of the ideology of progress, as relevant as ever, remains a central aspect of his production from his early writings to his death. At a time when the word progress has become a synonym of modernity, advancing like a locomotive on iron tracks, denouncing instead, with Benjamin, its catastrophic outcomes, can only contribute to a profound analysis of the contemporaneity in which we are immersed. We will therefore analyze paradigmatic occasions in which Benjamin, from his youthful years up to the Paris Passages and the Theses on the Concept of History, denounces how progress is, in reality, a regression to “something immemorially ancient that struts about in the guise of absolute novelty”.